Perang Salib: Analisis Sejarah dan Dampaknya terhadap Kristen dan Islam - Tamara Wita Batubara; Rangga Abetnego Simaremare; Landong Sihombing; Veronika Tumangger (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
The crusades are a part of history that has been passed through in religious life. For reasons of fighting over religious property rights and there are hidden reasons, namely political and economic. This research uses qualitative methods with library research by collecting various sources, data, and also trusted internet sources. This writing aims to find out the impact of the crusades on Islam and Christianity.